Automated real-time behavioral and physiological data acquisition and display integrated with stimulus presentation for fMRI - Voyvodic, James T.; Glover, Gary H.; Greve, Douglas; Gadde, Syam; FBIRN, The (Frontiers in Neuroinformatics, 2011)
Functional MRI (fMRI) is based on correlating blood oxygen-level dependent (BOLD) signal fluctuations in the brain with other temporal variables. Although the most common reference variable is the timing of a behavioral task performed during the scan, many other behavioral and physiological temporal variables can also influence fMRI signals. Variations in cardiac and respiratory functions in particular are known to contribute significant BOLD signal fluctuations. Variables such as skin conduction, eye movements, and other measures that may be relevant to task performance can also be correlated with BOLD signals and can therefore be used in image analysis to differentiate multiple components in complex brain activity signals. Combining real-time recording and data management of multiple behavioral and physiological signals in a way that can be routinely used with any task stimulus paradigm is a nontrivial software design problem. Here we discuss software methods that allow users complete control of paradigm-specific audio-visual or other task stimuli combined with automated simultaneous recording of multi-channel behavioral and physiological response variables, all synchronized with sub-millisecond temporal accuracy. We also discuss the implementation and importance of real-time display feedback to ensure data quality of all recorded variables. Finally, we discuss standards and formats for storage of temporal covariate data and its integration into fMRI image analysis. These neuroinformatics methods have been adopted for behavioral task control at all sites in the FBIRN multicenter fMRI study.